High-Risk Features Are Prognostic in dMMR/MSI-H Stage II Colon Cancer - Mohamed, Amr; Jiang, Renjian; Philip, Philip A.; Diab, Maria; Behera, Madhusmita; Wu, Christina; Alese, Olatunji; Shaib, Walid L.; Gaines, Tyra M.; Balch, Glen G.; El-Rayes, Bassel F.; Akce, Mehmet (Frontiers in Oncology, 2021)
Background: High-risk features such as T4 disease, bowel obstruction, poorly/undifferentiated histology, lymphovascular, perineural invasion, <12 lymph nodes sampled indicate poor prognosis and define high-risk stage II disease in pMMR stage II colon cancer (CC). The prognostic role of high-risk features in dMMR/MSI-H stage II CC is unknown. Similarly, the role of adjuvant therapy in high-risk stage II CC with dMMR/MSI-H (≥1 high-risk feature) has not been studied in prospective trials. The aim of this analysis of National Cancer Database (NCDB) is to evaluate the prognostic value of high-risk features in stage II dMMR/MSI-H CC. Methods: Univariate (UVA) and multivariate (MVA) Cox proportional hazards (Cox-PH) models were built to assess the association between clinical and demographic characteristics and overall survival. Kaplan-Meier survival curves were generated with Log-rank tests to evaluate association between adjuvant chemotherapy in high-risk and low-risk cohorts separately. Results: 2293 stage II CC patients have dMMR/MSI-H, of those 29.5% (n=676) had high-risk features. High-risk dMMR/MSI-H patients had worse overall survival (5-year survival and 95%CI 73.2% (67.3%-78.1%) vs. 80.3% (76.7%-83.5%), p=0.0001). In patients with stage II dMMR/MSI-H CC, high-risk features were associated with shorter OS along with male sex, positive CEA, Charlson Deyo Score>1, and older age. Adjuvant chemotherapy administration was associated with better OS regardless of high-risk features in dMMR/MSI-H (Log-rank test p=0.001) or not (p=0.0006). When stratified by age the benefit of chemotherapy was evident only in patients age >65 with high risk features. Conclusion: High-risk features are prognostic in the setting of dMMR/MSI-H stage II CC. Adjuvant chemotherapy may improve survival specifically in the patients >65 years and with high-risk features.